Case Report: Remission of schizophrenia using a carnivore ketogenic metabolic therapy with nutritional therapy practitioner support - Newiss, Moira (Frontiers in Nutrition, 2025)
This retrospective case report presents the use of a carnivore ketogenic diet by a subject with schizophrenia, supported by a nutritional therapy practitioner, resulting in remission. The narrative describes how ketogenic metabolic therapy can be implemented and optimized in difficult socio-economic circumstances, something not previously reported in the literature. Compliance with diet is reported using glucose and ketone blood markers. The qualitative impact of the therapy is explored from the subject’s perspective as well as the potential for collaboration between nutritional and mental health practitioners to help implement and sustain ketogenic therapies.